Clinical determination of the occlusal plane and its relation with orofacial measurements - Zeina M Ahmad; Inas A Jawad; Ahmed A Al-Ali (University of Mosul, College of Dentistry, 2007)
Aims: To determine the level and angulation of the occlusal plane of the artificial dental arch by measuring the level and angulation of the occlusal plane of completely dentulous subjects and to find the relation of these measurements to some of the vertical facial and intra oral dimensions. Materials and Methods: The sample of the study consisted from 54 completely dentulous adult subjects (24 female and 30 male) with class 1 normal occlusion aged 19-24 years. Dental casts were taken for each subject, the level and angulation of the occlusal plane, vertical facial, and intra oral dimensions were measured using digital vernier caliper and protractor. The data were analyzed with statistical package for social science program. Results: Sexual differences were found in the intra and extraoral measurements. Most of the measurements dealing with the occlusal plane level and angulation were correlated with each other and with facial measurements. Conclusions: The level and angulation of the occlusal plane of the maxillary and mandibular dental arches as measured on the dental casts are higher in maxilla than in mandible and the intra and extraoral vertical facial measurements are greater in male than female.